Tidal Current Energy Resources Assessment in the Patinti Strait, Indonesia - Novico, Franto; Sudjono, Evi Hadrijantie; Egon, Andi; Menier, David; Methew, Manoj; Pratama, Munawir Bintang (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Indonesia is currently intensively developing its renewable energy resource and targets at least 23% by 2025. As an archipelago country, Indonesia has the potential to benefit from its abundant renewable energy resources from its offshore regions. However, the short tidal range of mixed semi-diurnal and the suitable tidal turbine capacity may hinder marine renewable energy development in Indonesian waters. This paper presents higher-order hydrodynamic numerical models to provide spatial information for tidal current resource assessment of the Patinti Strait. The present study applied the hydrographic and oceanographic method to produce input of the numerical model. Based on the selected simulation analysis, the highest current speed could be identified around Sabatang and Saleh Kecil Island with up to 2.5 m/s in P1 and 1.7 m/s in P4. Besides, the operational hours for the two observation points are 69% and 74.5%, respectively. The results indicate that this location is of prime interest for tidal turbine implementation as an energy source, for medium capacity (300 kW) and high capacity (1Â MW).